Effectiveness of Quality of Seminar Services and Corporate Image on Consumer Satisfaction of Seminar Services - Puti Lenggo Ginny; Diana Silaswara; Rinintha Parameswari (eCo-Fin, 2022)
This research on the effect of service quality and company image on customer satisfaction with seminar services was prepared using the associative method to examine two or more variables. Data collection used is questionnaire data. Every company engaged in seminar and sales services is oriented to achieve maximum profit by using minimal data sources. Therefore, marketing as a part of the company's body has a very important role for the development and survival of the company itself.Image is the most important tangible asset owned by the company. A good image can support the company's competitiveness and can also be a protection in times of crisis. Besides that, a good image can also be an attraction for executives and increase the effectiveness of marketing strategies and save operational costs.This study aims to determine how much influence service quality has on consumer satisfaction and corporate image at the Seminar Service Company. It can be seen from the results of the calculation of the correlation coefficient, which is 0.523 which means strong and the calculation of the coefficient of determination of 27.4% affects the company's image to consumers. And it can be seen from t count of 4.607 and t table of 1,978 which is greater than t count.So, by knowing the response of service quality and company image to customer satisfaction at the Seminar Service Company, it is hoped that it can provide input to satisfy consumers in improving the quality of service and company image that has been carried out.